Cytotoxicity and nitric oxide inhibitory activities of Xanthones isolated from Calophyllum hosei Ridl. Issue 24 (17th December 2021) - Daud, Shaari; Karunakaran, Thiruventhan; Santhanam, Rameshkumar; Nagaratnam, Suman Raj; Jong, Vivien Yi Mian; Ee, Gwendoline Cheng Lian
Abstract: Previous studies on Calophyllum species have shown the existence of a wide variety of bioactive xanthones and coumarins. Phytochemical investigations carried out on the plant, Calophyllum hosei led to the isolation of eleven known xanthones, ananixanthone (1 ), 9-hydroxycalabaxanthone (2 ), dombakinaxanthone (3), thwaitesixanthone (4), caloxanthone B (5 ), trapezifolixanthone (6 ), β-mangostin (7), osajaxanthone (8 ), caloxanthone A (9), calozeyloxanthone (10) and rubraxanthone (11) . The structures of these compounds were identified and elucidated using spectroscopic techniques such as NMR and MS. The cytotoxicity and nitric oxide production inhibitory activities of selected xanthones as well as the extracts were tested against HL-60 cells and RAW 264.7 murine macrophages, respectively. Among all tested compounds, β-mangostin exhibited appreciable cytotoxicity against HL-60 cells with the IC50 value of 7.16 ± 0.70 µg/mL and rubraxanthone exhibited significant nitric oxide inhibitory activity against LPS induced RAW 264.7 murine macrophages with the IC50 value of 6.45 ± 0.15 µg/mL. Graphical Abstract: UF0001